(untitled) (Conference Zone, 2022)
Physiological and biochemical changes during the growth period of grain planted in the ground also occur in artificially grown grain. from environment to active life. The flour-like state of the reserve substances breaks down with the consumption of water and is easily attacked by enzymes. During cultivation, the consumption of nutrients increases. At the beginning, for consumption, substances that are quickly soluble in water and easily digestible are used, which are in small quantities in the murkat. Murtak consumes water-soluble substances, and then feeds on substances contained in grain.[1-10]